Política Nacional de Resíduos Sólidos: histórico, cenário da gestão e os acordos setoriais no estado de São Paulo - Fagliari, Raphael Augusto (Universidade Federal de São Carlos, 2017)
The National Policy of Solid Waste (NPSW), instituted by the federal law nº 12.305/2010, establishes the guiding principles, legal instruments and objectives to order the actions and practices of waste management in Brazil. Among the proposed principles and instruments, the shared responsibility for the products life cycle and the reverse logistic are inducers of a new management model and a great challenge as well. To assist in its operationalization, the NPSW institutes the Sectoral Agreements (SA) and, in São Paulo State, the SA were established by the Commitment Terms of Reverse Logistics (CTRL). Seeking to bring this scenario to light, the current research proposes to present and analyze the implementation of CTRL in São Paulo State. For this, it is presented the historical of the 12.305/2010 law approval process and the waste management scenario post-NPSW. The data and information collection occurred through bibliographic and documentary review, and the CTRL case study was developed with an application of questionnaires and interviews. The State of São Paulo presents 10 signed CTRL, with 08 sectors participating in this research. Inconsistencies were identified regarding the definition of targets and the results obtained by the sectors, which adopted, in most, different metrics. The Secretariat for the Environment of São Paulo State played a fundamental role in stimulating and directing the terms, being the main responsible for establishing them juridically in a legal instrument, acting also in the definition of targets. The participation of different actors in the realization of shared responsibility is still deficient, with a greater accountability to manufacturers. The involvement of cooperatives and public authorities is not a reality yet, which have importance and role beyond the perception of CRTL subscribers. Most of the sectors use support tools (software and GIS) and affirm to have reached the established targets, having as the main difficulty the low interest and participation of the others chain members. It is concluded that the NPSW, despite the slow evolution, should stimulate new and necessary solid waste management practices in Brazil, having the sectoral agreements as a pillar for the reverse logistics and shared responsibility effectiveness.
Keywords: Política Nacional de Resíduos Sólidos; Logística reversa; Acordos setoriais; Resíduos sólidos; Responsabilidade compartilhada; Termos de compromisso de logística reversa; Responsabilidade pós-consumo; National Policy of Solid Waste; Reverse logistics; Sectoral agreements; Solid waste; Shared responsibility; Commitment terms of reverse logistics; Postconsumer responsibility; CIENCIAS BIOLOGICAS